Using of aluminium slags and products of their pro‑cessing in metallurgical production - L. V. Tribushevskiy; B. M. Nemenenok; G. A. Rumiantseva; A. V. Arabey (Литьë и металлургия)
The work contains the results of the analysis of technical literature and author’s research on the use of aluminium slags and products of their processing in metallurgical production. It has been shown that the bulk of reagents derived from secondary aluminum production wastes (APWs) are used with increased sodium and potassium chloride. This creates some inconvenience for out‑of‑furnace steel treatment due to the increased chloride content in the working area. It is proposed for steel processing to use APWs formed during flux‑free melting or dump aluminium slags. This allows to reduce the content of salt fluxes residues to 1.0–1.5 % and to improve working conditions at ladle furnaces when liquefying refining slags.